Guest satisfaction level of front office service during covid-19 in renaissance bali uluwatu resort & spa - Paramita, Ni Made Mira; Winia, I Nyoman; Suarta, I Ketut; Septevany, Elvira (Institut Pariwisata dan Bisnis Internasional, 2022)
The purpose of this research is to examine the level of guest satisfaction with the services of Front office staff at Renaissance Bali Uluwatu Resort & Spa. The population is 60 respondents with the sample of method accidental sampling. The method of analysis used is the ServQual Test to describe the gap between expected service quality (expectations) and reality (perceptions). Furthermore, it is analyzed by Important-Performance Analyzes (IPA) using a Cartesian Diagram to identify services based on the level of importance and customer satisfaction with the service quality. The attributes that produce a positive average gap are shown in the dimensions of reliability, assurance, and empathy, which means that the service is satisfactory. On the other hand, the attributes that need to be improved and produce a negative average gap are tangible and responsiveness dimensions.